Biogeographic Evaluation of Mediterranean Sclerophyllous Forest with Palm Trees (Jubaea Chilensis) in the Quiteño River Bassin, from the Application of the Lanbioeva Evaluation Method [Valoración Biogeográfica del Bosque Mediterráneo Esclerófilo Con Palmeras (Jubaea Chilensis Mol (Baillon)) en la Cuenca del Quiteño (Chile), a Partir de la Aplicación del Método de Valoración Lanbioeva] - Quintanilla-Perez, V (CSIC Consejo Superior de Investigaciones Cientificas, 2016)
The present paper is based on research work that has been carried out for more than 20 years with the purpose of consolidating a method of biogeographic valuation of different plant scenes at a global scale. A few years ago, as a result of a research stay, different units of the Mediterranean environment of Chile were assessed. Among the results, the sclerophyllous Mediterranean forest with palms (Jubaea chilensis) clearly called one s attention because it not only achieved the highest scores in this setting, but it got the absolute record to date. The paper is centered on, presents and analyzes the results obtained in that unit, but this time with systematic inventories and assessments made in 2015. The base study area is concentrated in a small microbasin, El Quiteño, in the coastal mountains of Viña del Mar. The natural and cultural values do not differ from some formations of the surrounding, even from formations situated in the European setting, yet the conservation priority shoots up taking into account that the participations referred to the global threat factor are very high. Copyright: © 2016 CSIC This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial (by-nc) Spain 3.0 License.